Ukuran Perusahaan Memoderasi Hubungan Green Accounting, Intellectual Capital dan Kepemilikan Manajerial Terhadap Nilai Perusahaan - Suripto Suripto; Putri Anisya Islami (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to explore how green accounting, intellectual capital, and managerial ownership can affect firm value, with firm size acting as a moderating variable. The focus of this research is on companies listed in the Jakarta Islamic Index (JII) from 2018 to 2022, with a sample of 15 companies representing 75 data points. The analysis method used is multiple linear regression. The hypothesis testing results show that green accounting has a significant effect on firm value, as it can enhance the company's reputation and attractiveness to consumers, investors, and the broader public. Conversely, intellectual capital does not show a significant impact on firm value, possibly due to investors' lack of understanding of how companies manage their intellectual assets. Managerial ownership has a significant impact on firm value because managers' stock ownership strengthens the alignment between managerial and shareholder interests. This research provides new insights into the factors affecting firm value and highlights the importance of green accounting and managerial ownership in enhancing firm value in a competitive market.